ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH RISK MANAGEMENT IN METAL INDUSTRY PRODUCTION AREAS USING THE HIRA METHOD - Irianingtyas, Riza; Bimantara, Arya; Chahyadhi, Bachtiar; Rahmania, Nima Eka Nur (Nurse and Health: Jurnal Keperawatan, 2025)
Background : The informal metal industry poses a high risk of hazards but often escapes oversight of Occupational Safety and Health (K3) standards. The lack of systematic risk management in these environments exposes workers to a variety of hazards, ranging from ergonomic, mechanical, physical, and chemical, all of which can potentially lead to accidents and occupational illnesses. Objective: The purpose of the research is to identify potential hazards, assess the level of risk in each production area, and formulate effective control alternatives to minimize work incidents. Methods: The research method used was descriptive quantitative with the Hazard Identification and Risk Assessment (HIRA) approach. This approach was used to analyze all activities in nine production areas through the stages of hazard identification, likelihood and severity assessment, and risk level determination. Data was collected through direct observation and worker interviews, and validated using secondary data from Job Safety Analysis (JSA) and previous incident reports. Results: The research results showed that there were 11 findings of high hazard risks, 11 moderate hazard risks and 7 low hazard risks in all production areas. Conclusion: It can be concluded that the application of the HIRA method is essential for risk management in the informal metal industry. It is recommended to implement hierarchical controls, ranging from engineering controls such as the installation of machine guards and ventilation systems, to administrative controls such as the development of stricter SOPs and regular OHS training.